Teacher training in Higher Education to improve learning assessment: theoretical issues and research outcomes - Cristina Coggi; Paola Ricchiardi (Firenze University Press, 2020)
In recent decades, University has undergone various changes, in relation to the purposes, functions and targets of its actions, and has called to transit from a cultural transmission, centred on content and dedicated to the few, to a mass education, aimed at promoting significant learning and skills as much as possible. These innovations must be followed by as many important transformations in methods and tools adopted by the professors in both teaching and evaluation. Because university teachers are able to review concepts and practices according to the new functions attributed to University, appropriate training courses should be organized. We present the emerging issues in this regard, in particular by focusing on the problematic aspects of the evaluation. We therefore describe the intervention carried out about this topic by the University of Turin (IRIDI Project) and we take into account the main results obtained.   Formare i docenti universitari alla valutazione degli apprendimenti: istanze teoriche ed esiti di ricerca Negli ultimi decenni l'università è stata oggetto di numerosi cambiamenti, in relazione agli scopi, alle funzioni, e ai destinatari delle sue azioni, ed è stata chiamata a transitare, da una trasmissione culturale, centrata sui contenuti, dedicata a pochi, ad una formazione di massa, volta a promuovere apprendimenti significativi e competenze quanto più possibile. A queste innovazioni devono seguire altrettante importanti trasformazioni dei metodi e degli strumenti adottati dai docenti universitari sia nella didattica che nella valutazione. Perché chi insegna sia in grado di rivedere concezioni e pratiche secondo le nuove funzioni attribuite all'università, è opportuno che siano organizzati percorsi adeguati di formazione. Presenteremo le istanze emergenti a tal proposito, in particolare centrandoci sugli aspetti problematici della valutazione. Descriveremo quindi un intervento, realizzato in quest'ambito dall'Università di Torino (Progetto IRIDI) e daremo conto dei principali esiti ottenuti.